If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 5x + 10 Reorder the terms: 15 = 10 + 5x Solving 15 = 10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 15 + -5x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 15 + -5x = 10 + 0 15 + -5x = 10 Add '-15' to each side of the equation. 15 + -15 + -5x = 10 + -15 Combine like terms: 15 + -15 = 0 0 + -5x = 10 + -15 -5x = 10 + -15 Combine like terms: 10 + -15 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 12-7x=46-21x | | 2z+10=70 | | -x(3x+2)=5 | | 12w^2=28w+5 | | x^4y^2-2x^2y+1=0 | | 4x^2-8x+10=0 | | x^4y^2-2x^2y-1=0 | | -8[-3-(-5+6j)]=4(12j-4) | | 4(w-4)(w-1)-1(w-4)=-5(w-1) | | 8m=3m+2 | | 6x-10y=30 | | 8m=3n+2 | | 4(w-4)(w-1)=-5(w-1) | | -16x^5-36x^3=0 | | (3-5x)-(2x-1)= | | 3t/4-t/2=1 | | -8x-24+2x+6=7x+10 | | 3(v-8)=5v-38 | | X=79x | | -7y+4=8(y+8) | | u^2+4u-21= | | -4(y-6)=8y+48 | | 7-2x=y | | -9u+49=8(u+4) | | 5(x-5)=-8x-38 | | -8(x+3)+2x+6=7x+10 | | .28-.02(x+3)=-.03(1-x) | | 7y+32= | | -6(x+2)+4x+7=7x+11 | | 15+8= | | -24+8x=10x+1 | | -5s+2(s-7)+8s=5s-14 |